منهج تعليم الترجمة في ضوء الإطار الوطني الإندونيسي للمؤهلات - Satibi, Satibi (STAINI Press, 2022)
This study aims to: (1) describe the preparation of the translation teaching curriculum at the Tarjamah Department of UIN Syarif Hidayatullah Jakarta in the KKNI perspective, (2) measure the suitability of the translation teaching curriculum at the Tarjamah Department in the KKNI perspective. This type of research is qualitative research with a case study approach. The researcher used the Miles & Hubberman interactive data analysis model, going through the stages: collecting data, data reduction techniques, data presentation, and verification. Data was collected by interview, observation, documentation and triangulation methods. The results showed that: (1) the preparation of the curriculum for teaching translation in the Tarjamah department was carried out by each subject lecturer through stages systematically based on the KKNI, (2) the curriculum for teaching translation in the Tarjamah department was in accordance with the criteria in the KKNI